Pengaruh Work-family Conflict terhadap Turnover Intention pada Karyawan Manufacturing Industry - Raihan Ahmad Razaki; Anna Rozana (UNISBA Press, 2022)
Abstract. Employee turnover is the biggest problem for companies in recent years. Turnover intention is considered as the main predictor to prevent employees turnover. Turnover intention is defined as the employee's desire to leave the company. One of the factors that can influence turnover intention is work-family conflict. Conflict in which the role pressures of the work and family domains contradict each other in some way. This study aims to determine the influence of work-family conflict on turnover intention in manufacturing industry employees. The method used is quantitative with a total of 81 respondents. The data collection in this study used the Work-family Conflict Scale measuring instrument for the work-family conflict variable and the turnover intention measurement tool compiled by Maya Sita Darlina M.Si (2012) for the variable turnover intentions. The analysis technique used is multiple linear regression. The results showed that the work-family conflict variable contributed significantly to the positive direction, which was 38.8% on the turnover intention variable. Abstrak. Turnover karyawan masih menjadi masalah terbesar bagi perusahaan dalam beberapa tahun terakhir. Dalam mengatasi masalah ini turnover intention dianggap sebagai prediktor utama untuk dapat mencegah karyawan melakukan turnover. Turnover intention didefinisikan sebagai keinginan karyawan untuk meninggalkan perusahaan. Salah satu faktor yang dapat mempengaruhi turnover intention yaitu work-family conflict. Konflik di mana tekanan peran dari pekerjaan dan domain keluarga saling bertentangan dalam beberapa hal. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh work-family conflict terhadap turnover intention pada karyawan manufacturing industry. Metode yang digunakan adalah kuantitatif dengan jumlah responden sebanyak 81. Pengumpulan data pada penelitian ini menggunakan alat ukur Work-family Conflict Scale untuk variabel work-family conflict dan alat ukur turnover intention yang di susun oleh Maya Sita Darlina M.Si (2012) untuk variabel turnover intention. Teknik analisis yang digunakan adalah regresi linier berganda. Hasil penelitian menunjukkan variabel work-family conflict menyumbang pengaruh yang signifikan dengan arah positif yaitu sebesar 38,8% terhadap variabel turnover intention.